International investment rule-making stocktaking, challenges and the way forward (UNCTAD series on international investment policies for development, 2008)
This book reviews sixty years of international investment rule-making and identifies main trends in current treaty practice, as well as the core characteristics of the existing universe of International Investment Agreements (IIAs) at the beginning of the 21st century. Based on this analysis, the third part describes the main challenges for policy makers and IIA negotiators deriving from the present IIA system, and makes a number of suggestions on how to deal with them. The Fourth part contains a brief outlook concerning the future evolution of the IIA universe.--Publisher's description